Highly effective hydrogen isotope separation in nanoporous metal-organic frameworks with open metal sites: Direct measurement and theoretical analysis - Oh, Hyunchul; Savchenko, Ievgeniia; Mavrandonakis, Andreas; Heine, Thomas; Hirscher, Michael (ACS nano, 2014)
Separating gaseous mixtures that consist of very similar size is one of the critical issues in modern separation technology. Especially, the separation of the isotopes hydrogen and deuterium requires special efforts, even though these isotopes show a very large mass ratio. Conventionally, H/D separation can be realized through cryogenic distillation of the molecular species or the Girdler-sulfide process, which are among the most energy-intensive separation techniques in the chemical industry. However, costs can be significantly reduced by using highly mass-selective nanoporous sorbents. Here, we describe a hydrogen isotope separation strategy exploiting the strongly attractive open metal sites present in nanoporous metal-organic frameworks of the CPO-27 family (also referred to as MOF-74). A theoretical analysis predicts an outstanding hydrogen isotopologue separation at open metal sites due to isotopal effects, which has been directly observed through cryogenic thermal desorption spectroscopy. For H2/D2 separation of an equimolar mixture at 60 K, the selectivity of 12 is the highest value ever measured, and this methodology shows extremely high separation efficiencies even above 77 K. Our theoretical results imply also a high selectivity for HD/H2 separation at similar temperatures, and together with catalytically active sites, we propose a mechanism to produce D2 from HD/H2 mixtures with natural or enriched deuterium content. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20
Keywords: gas adsorption; hydrogen isotopes; isotope separation; metal-organic frameworks; nanoporous materials; quantum sieving